Food Restriction Reverses the Hyper-Muscular Phenotype and Force Generation Capacity Deficit of the Myostatin Null Mouse - Matsakas, A.; Romanello, V.; Sartori, R.; Masiero, E.; Macharia, R.; Otto, A.; Elashry, M.; Sandri, M.; Patel, K. (International Journal of Sports Medicine, 2013)
Food restriction has a great impact on skeletal muscle mass by inducing muscle protein breakdown to provide substrates for energy production through gluconeogenesis. Genetic models of hyper-muscularity interfere with the normal balance between protein synthesis and breakdown which eventually results in extreme muscle growth. Mutations or deletions in the myostatin gene result in extreme muscle mass. Here we evaluated the impact of food restriction for a period of 5 weeks on skeletal muscle size (i. e., fibre cross-sectional area), fibre type composition and contractile properties (i. e., tetanic and specific force) in myostatin null mice. We found that this hyper-muscular model was more susceptible to catabolic processes than wild type mice. The mechanism of skeletal muscle mass loss was examined and our data shows that the myostatin null mice placed on a low calorie diet maintained the activity of molecules involved in protein synthesis and did not up-regulate the expression of genes pivotal in ubiquitin-mediated protein degradation. However, we did find an increase in the expression of genes associated with autophagy. Surprisingly, the reduction on muscle size was followed by improved tetanic and specific force in the null mice compared to wild type mice. These data provide evidence that food restriction may revert the hyper-muscular phenotype of the myostatin null mouse restoring muscle function.
Keywords: myostatin; muscle mass; muscle strength; nutritional intervention